2009
DOI: 10.1007/s00787-009-0011-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in hypothalamic–pituitary–adrenal axis functioning among children with ADHD predominantly inattentive and combined types

Abstract: Some evidence suggests that the HPA axis may be dysfunctional in children with attention-deficit/hyperactivity disorder (ADHD). The aim of this study was to investigate whether a different pattern of HPA axis activity is found between the inattentive (I) and combined (C) subtypes of ADHD, in comparison with healthy control children. A total of 100 prepubertal subjects [52 children with ADHD combined type (ADHD-C), 23 children with ADHD predominantly inattentive type (ADHD-I), and 25 healthy control subjects] w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 68 publications
4
31
0
Order By: Relevance
“…However, at 25/30 min post-challenge (cort_lastP) cortisol levels were elevated, although with considerable more variability, in the TYPs and ADHDs groups to a greater extent than in either of the other non-SOR groups. This cortisol response pattern in our children with ADHDs had been identified in our earlier work, and stands in contrast to other studies which found that children with ADHD and externalizing disorders tend to show blunted cortisol levels in response to a challenge or stressor (King et al, 1998; Hong et al, 2003; van West et al, 2009). The children in this study with ADHDt did show a more attenuated cortisol response, suggesting that SOR may influence the cortisol response in children with ADHD.…”
Section: Discussionsupporting
confidence: 49%
“…However, at 25/30 min post-challenge (cort_lastP) cortisol levels were elevated, although with considerable more variability, in the TYPs and ADHDs groups to a greater extent than in either of the other non-SOR groups. This cortisol response pattern in our children with ADHDs had been identified in our earlier work, and stands in contrast to other studies which found that children with ADHD and externalizing disorders tend to show blunted cortisol levels in response to a challenge or stressor (King et al, 1998; Hong et al, 2003; van West et al, 2009). The children in this study with ADHDt did show a more attenuated cortisol response, suggesting that SOR may influence the cortisol response in children with ADHD.…”
Section: Discussionsupporting
confidence: 49%
“…For example, it was suggested that catecholamine levels are altered in urine samples of patients with ADHD (Salavessa et al 2009) and that they may also exhibit an altered cortisol response (van West et al 2009). …”
Section: Proteomicsmentioning
confidence: 97%
“…Cortisol then acts on the hypothalamus, pituitary, and hippocampus to inhibit its own production in a negative feedback loop. It has been reported that children with ADHD have a blunted cortisol response to psychosocial stressors, a decreased cortisol awakening response (CAR), or lower plasma daytime cortisol (King et al 1998;Ma et al 2011;Randazzo et al 2008;Scerbo and Kolko 1994;van West et al 2009), though there is considerable inconsistency between studies (Freitag et al 2009;Hastings et al 2009;Snoek et al 2004).…”
Section: Introductionmentioning
confidence: 98%